Development of graphene capped silicon–silicon oxide core–shell nano-structure: Charge trapping characteristics at the interfaces. (December 2018) - Nandi, Anupam; Biswas, Susmita; Chakrabarty, Sudipta; Majumdar, Sanhita; Saha, Hiranmay; Saini, Mahesh; Hossain, Syed Minhaz
Graphical abstract: Highlights: Graphene encapsulated Si–SiO X core–shell nanostructure (SiNC) has been synthesized by simple in situ co-reduction wet chemical techniques. Two terminal device with symmetric architecture has been fabricated by putting the nanocomposite between two Al electrodes. Kelvin probe AFM studies show development of built in potential at the graphene–SiNC interface that leads to asymmetric I – V characteristics of the device. Light I – V curve of the nanocomposite supports photovoltaic response with high open circuit voltage. Abstract: Colloidal suspension of nano-dimensional Si–SiO X core–shell has been synthesized by step down mechanical process followed by thermo-chemical treatments. Graphene oxide (GO) has been synthesized by modified hummer's method. A wet chemical in situ co-deposition/reduction technique has been performed in amine rich medium to encapsulate the Si–SiO X core–shell nanostructure by amine functionalized reduced graphene oxide (af-rGO). The presence of silicon nano-crystals and af-rGO in the nanocomposite has been confirmed by Raman, FTIR and XRD studies. Core–shell structure of the nanocomposite has been confirmed by field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). A simple two terminal device has been fabricated with the synthesized nanocomposite in between two aluminium electrodes on glass substrate. In spite of the symmetric architecture of the device, the current–voltage ( I – V ) characteristics exhibits an asymmetry in nature, suggesting the formation of rectifying junction at the interfaces. Surface potential mapping has been obtained by Kelvin probe force microscopy (KPFM) to reveal the developed built-in potential at the interfaces. A chemical model has been postulated that assures the formation of dipoles and traps at the respective af-rGO/SiO X and SiO X /Si interfaces. The role of trapped charges has been established by solving Poisson's equation, validated by the trap density estimation from the capacitance–voltage ( C – V ) curve. This newly developed nano-structure has immense potential in the field of photovoltaics and electronics as a basic building block.